Impact and management of weed flora in cassava in west coast region of Peninsular Malaysia - A'Ihi, Abdullahi Musa (2018)
Cassava (Manihot esculenta Crantz) is an important root crop providing carbohydrate for more than 200 million people mostly in Africa and to some extent in Asia and Latin America. Cassava production in the tropics is confronted with several problems of which weed is the most significant because it causes yield loss. Weeds affecting cassava adversely by competing for light, nutrients, water and space. This research work is embarked upon with the objectives; i. To identify weed species that infest cassava crop, ii. To estimate the yield loss in cassava caused by weed infestation and competition, iii. To determine the critical periods of weed competition in cassava and, iv. To evaluate the most appropriate and efficient weeds management strategy in cassava. Weed survey was conducted in the cassava fields across west coast of Peninsular Malaysia. A total of 55 weed species were identified in the survey; 22 species belonging to 14 families in Selangor, 16 species belonging to 14 families in Johor and 17 species belonging to 15 families in Perak. The additional one (1) species observed in Perak was the spiderwort species of Commelinaceae family. Poaceae (29.1%) and Asteraceae (27.3%) families dominated cassava fields in peninsular Malaysia. Other families were Cyperaceae (9.1%), Euphorbiaceae and Rubiaceae (5.5% each), Convoluvolaceae, Amaranthaceae and Mimosaceae (3.6% each), Malvaceae, Acanthaceae, Leguminaceae, Boraginceae, Capparidaceae, Portulacaeae and Commelinaceae (1.8% each). Study on the competition between three varieties of cassava- Sri Kanji 2, Sri Pontian and Sri Medan versus weed species showed that cassava yields were significantly reduced in the weedy plot as follows: Sri Medan (79.4% yield loss) > Sri Kanji 2 (74.9.% yield loss) > Sri Pontian (69.7% yield loss). The results of critical periods of weed competition study showed that weed free period in cassava is between 20-170 days after planting at 5% tolerable yield loss and 30-155 days after planting at 10% tolerable yield loss. Study on weed management showed that herbicide treatments are better than mechanical in efficacy and systemic herbicides are better than the contact herbicides. It also showed that diuron is the overall best herbicide for controlling weeds in cassava field.